ANALISIS TERHADAP SOAL PENILAIAN AKHIR SEMESTER TINGKAT SD/MI DALAM PERSPEKTIF HIGH ORDER THINK SKILLS - Yudha Andana Prawira; Titim Kurnia (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
The National Education World is currently trying to improve the ability of its students to think critically and creatively. One of these efforts has been pursued through evaluations that also lead to critical reflection. This research is a descriptive analysis of the final semester evaluation questions that are examined from the point of view of high-level thinking [HOTS]. The reference to the HOTS criteria is that the researcher refers to the opinions of King and his friends. From the manuscript data, the issues examined are samples from the Bandung area. The results of the analysis show that 10 out of 15 HOTS ranges proposed by King are already included in the scripts made by the teachers. On the one hand, it shows the teacher's creativity in compiling questions. On the other hand, all these questions do not refer to the HOTS criteria as planned. Therefore, there is a need to increase teachers' skills in compiling scripts as HOTS. This increase can be done through teacher training.Key words: Evaluation, HOTS, critical thinking and creativity thingking